Sodium azide bindings to goat probiotic - Apas, Ana Lidia (2011)
In a previous paper the effect of probiotic supplementation on the diminution of mutagenic compounds in gut goat were determined in vivo (Apas et al 2010). In addition, the diminution of putrescine, a gut cancer marked was observed. In order to study if the antimutagenic effect could be due to the absorption of mutagen by probiotic strains, we study the probiotic binding. The strains used in the probiotic mix, Enterococcus faecium DDE39, Lactobacillus alimentarius DDL48, Lactobacillus reuteri DDL 19, were challenger in the presence of sodium azide (15¦Ìg/mL) during two hours at 37¡ãC. After this time, using the AMES test and the strains Salmonella typhimurium TA 100 and Salmonella typhimurium TA 98, as biological mutagen indicator, the binding was evaluated. The results indicated that the binding of Lactobacillus reuteri DDL 19, Enterococcus faecium DDE39 and Lactobacillus alimentarius DDL48 was of 74%, 69% and 59%, respectively using as bioindicator the strain Salmonella typhimurium TA 100 and 72, 72 and 44% using as indicator Salmonella typhimurium TA 98 The goat probiotic strains used in this study have shown high antimutagenicity and binding properties.